2002
DOI: 10.1103/physreva.65.042713
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the absolute partial and total cross sections for electron-impact ionization of the rare gases

Abstract: Accurate values of the electron-impact ionization cross sections for the rare gases are needed in a variety of contexts. However, despite numerous investigations over many decades, uncertainty as to the correct values has persisted. The pioneering total-cross-section measurements of Rapp and Englander-Golden are generally regarded as the most reliable but no comprehensive study has independently verified their correctness. In this paper, measurements of electron-impact ionization cross sections of helium, neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
222
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(262 citation statements)
references
References 53 publications
32
222
1
1
Order By: Relevance
“…We have used 2.51 × 10 −16 cm 2 as the Ar cross section. 34 The measurements for Ar were carried out by flowing the gas through the same oven and the capillary tube used for making measurements on the sample molecules. The pressure of Ar behind the capillary was measured using a capacitance manometer, while the pressure for the sample molecules was determined by measuring the temperature accurately and using the vapour pressure data of the samples given in Table I.…”
mentioning
confidence: 99%
“…We have used 2.51 × 10 −16 cm 2 as the Ar cross section. 34 The measurements for Ar were carried out by flowing the gas through the same oven and the capillary tube used for making measurements on the sample molecules. The pressure of Ar behind the capillary was measured using a capacitance manometer, while the pressure for the sample molecules was determined by measuring the temperature accurately and using the vapour pressure data of the samples given in Table I.…”
mentioning
confidence: 99%
“…This is primarily due to the fact that Ne has a much lower electronimpact ionization cross section σi over the entire electron-energy range. 10 Noble-gas σi values exhibit, by definition, a threshold at ) and the threshold is highest for Ne (see Table 1). At electron energies Ee > ) , σi vs. Ee curves have broad maxima, which for Ne occurs at ~160 eV compared to 70-90 eV for the heavier noble gases.…”
Section: Iiia Discharge Characteristicsmentioning
confidence: 99%
“…Here, the addition of small amounts of the reactive gas N2 to the C/Ne discharge catalyzes the dissociation and ionization of N2 [13,22]. This is attributed to metastable states of Ne (Ne*) at 16.62 eV and 16.71 eV that exceed the ionization potential of N2 ( = 15.6 eV) and N ( = 14.53 eV).…”
Section: Introductionmentioning
confidence: 99%
“…
A comparative study of direct current magnetron sputtering and high power impulse magnetron sputtering processes for CNX thin film growth with different inert gases, 2016, Diamond and related materials, (64), [13][14][15][16][17][18][19][20][21][22][23][24][25][26]
ABSTRACTReactive direct current magnetron sputtering (DCMS) and high power impulse magnetron sputtering (HiPIMS) discharges of carbon in different inert gas mixtures (N2/Ne, N2/Ar, and N2/Kr)were investigated for the growth of carbon-nitride (CNx) thin films. Ion mass spectrometry showed that energies of abundant plasma cations are governed by the inert gas and the N2-to-inert gas flow ratios.
…”
mentioning
confidence: 99%
See 1 more Smart Citation